(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article contains Aymad Yassavi’s proverbs about love and romance, as well as stories and narrations that reveal their essence. Different views on Yassavi’s rank of love are explained, and the description of divine love is interpreted as a precious power.